Racial Diversity, Electoral Preferences, and the Supply of Policy: The Great Migration and Civil Rights - Alvaro Calderon; Vasiliki Fouka; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
Between 1940 and 1970 more than 4 million African Americans moved from the South to the North of the United States, during the Second Great Migration. This same period witnessed the struggle and eventual success of the civil rights movement in ending institutionalized racial discrimination. This paper shows that the Great Migration and support for civil rights are causally linked. Predicting Black inflows with a version of the shift-share instrument, we find that the Great Migration increased support for the Democratic Party and encouraged pro-civil rights activism in northern and western counties. These effects were driven by both Black and white voters, and were stronger in counties with a lower history of discrimination and with a larger working class and unionized white population. Mirroring the changes in the electorate, non-southern Congress members became more likely to promote civil rights legislation. Yet, these average effects mask heterogeneity in the behavior of legislators, who grew increasingly polarized along party lines on racial issues. Overall, our findings indicate that the Great Migration promoted Black political empowerment outside the South. They also suggest that, under certain conditions, cross-race coalitions can be major drivers of social and political change.
Keywords: D72; J15; N92; 330; diversity; civil rights; great migration; race